Brassinosteroids play a critical role in the regulation of pesticide metabolism in crop plants - Zhou, Yanhong (Sci Rep, 2015)
Pesticide residues in agricultural produce pose a threat to human health worldwide. Although the detoxification mechanisms for xenobiotics have been extensively studied in mammalian cells, information about the regulation network in plants remains elusive. Here we show that brassinosteroids (BRs), a class of natural plant hormones, decreased residues of common organophosphorus, organochlorine and carbamate pesticides by 30–70% on tomato, rice, tea, broccoli, cucumber, strawberry, and other plants when treated externally. Genome-wide microarray analysis showed that fungicide chlorothalonil (CHT) and BR co-upregulated 301 genes, including a set of detoxifying genes encoding cytochrome P450, oxidoreductase, hydrolase and transferase in tomato plants. The level of BRs was closely related to the respiratory burst oxidase 1 (RBOH1)-encoded NADPH oxides-dependent H(2)O(2) production, glutathione biosynthesis and the redox homeostasis, and the activity of glutathione S-transferase (GST). Gene silencing treatments showed that BRs decreased pesticide residues in plants likely by promoting their metabolism through a signaling pathway involving BRs-induced H(2)O(2) production and cellular redox change. Our study provided a novel approach for minimizing pesticide residues in crops by exploiting plants' own detoxification mechanisms.